2023
DOI: 10.1155/2023/3542165
|View full text |Cite
|
Sign up to set email alerts
|

Metal Fractionation and Leaching in Soils from a Gold Mining Area in the Equatorial Rainforest Zone

Abstract: In this article, a modified BCR procedure and a column leaching test were used to examine the bioavailability and mobility of heavy metals in soils collected from a gold mining area in Ghana. The results for the fractionation of Cd, Cr, Fe, and Mn indicated that high percentages of metals were found in the residual fraction. This implies that the concentrations of metals in the soil are stable under normal environmental conditions. The bioavailability of metals in the soils declined in the following order: Mn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…The stability of the residue fraction in terms of content before and after leaching indicates that rainwater leaching over three years had minimal impact on altering the form of Cr within the soil lattice. Sarpong et al [ 45 ] also found that compared to Cd and Mn, Cr in the soil remains predominantly in the oxidizable and residual fractions. However, the increased content of the oxidizable fraction after leaching suggests that a small portion of water-soluble CrO 4 2− transformed into a more stable oxidizable fraction.…”
Section: Discussionmentioning
confidence: 99%
“…The stability of the residue fraction in terms of content before and after leaching indicates that rainwater leaching over three years had minimal impact on altering the form of Cr within the soil lattice. Sarpong et al [ 45 ] also found that compared to Cd and Mn, Cr in the soil remains predominantly in the oxidizable and residual fractions. However, the increased content of the oxidizable fraction after leaching suggests that a small portion of water-soluble CrO 4 2− transformed into a more stable oxidizable fraction.…”
Section: Discussionmentioning
confidence: 99%